(untitled) (Ameghiniana, 2018)
The genus Neoglyptatelus Carlini, Zurita, Scillato-Yané, Sánchez, and Aguilera has been considered a member of Glyptatelinae, a group encompassing the purportedly basal-most glyptodonts. It is up to now represented by two species from Colombia: Neoglyptatelus originalis Carlini et al., from the middle Miocene (a carapace fragment, isolated osteoderms and postcranial bones), and Neoglyptatelus sincelejanus Villarroel and Clavijo, from the middle or late Miocene (a partial carapace and a caudal armor). More scarce material assigned to this genus was recovered from the late Miocene of Uruguay and Brazil. In this article, we describe a new species, Neoglyptatelus uruguayensis, from the late Miocene Camacho Formation, Uruguay, based on an almost complete carapace and several postcranial bones. We conducted a phylogenetic analysis based on 167 morphological characters (23 new ones and 144 from previous analysis) scored for 19 taxa, encompassing some of the best known glyptodontid genera, one pampathere and four armadillos (including the enigmatic genus Pachyarmatherium Downing and White). In the most parsimonious tree that was obtained, Neoglyptatelus forms a clade with Pachyarmatherium (Pachyarmatheriidae), which is the sister group of the glyptodonts + pampatheres clade; consequently, it is not a glyptodont, as previously believed. This result, together with the known stratigraphic and geographic distribution of Neoglyptatelus and Pachyarmatherium, suggests that this new cingulate clade originated in South America and that Pachyarmatherium reached North America during the Plio–Pleistocene. The carapace of Neoglyptatelus and Pachyarmatherium comprises pelvic and scapular shields overlapping each other without separate intervening transverse mobile bands, an arrangement that differentiates both genera from the remaining cingulates.